NANOMEDICINE AND AI: A PROMISING ALLIANCE FOR PERSONALIZED CANCER TREATMENT (International Journal of Food and Nutritional Sciences, 2022)
Pharmaceutical nanotechnology is the pioneering, recently emerging field of medical knowledge that deals with using nanoscale accessories as medicinal delivery systems and/or standalone equipment. Nano-delivery devices can be utilized to improve the focused, point-specific administration of precise medications. Nanotechnology and artificial intelligence (AI) are two different disciplines that are essential for implementing the idea of perfection medication adapting the fashionable therapy for each cancer instance. Recent crossover between these two domains is allowing for greater case data access and improved nanomaterial creation for the ideal cancer medication. A case-specific complaint profile is put together using individual nanoparticles, and this profile is then utilized by a number of remedial nanotechnologies to improve the treatment's results. Though the logical design of individual and remedial platforms, as well as study of their relationship, are exceedingly difficult because to substantial intratumor and interpatient heterogeneity. Utilizing pattern analysis and bracket algorithms for improved individual and remedial delicacy, the integration of AI techniques can close this gap. By optimizing material packets in regard to predicted relationships with the target medication, natural fluids, vulnerable system, vasculature, and cell membranes, all of which impact therapeutic efficacy, nanomedicine design also benefits from the operation of AI. The benefits and promise of nanotechnology combined with AI to the future of the perfect cancer medication are then examined, followed by a description of abecedarian generalizations in AI.